THE ANALYSIS OF STRUCTURE SHIFT IN THE ENGLISH TRANSLATION OF THESIS ABSTRACTS FOUND AT TEACHER TRAINING AND EDUCATION FACULTY HALU OLEO UNIVERSITY - Supriyatno, Iwan (Universitas Halu Oleo, 2019)
This study is an attempt to contribute in the study of translation shift. The goal is to find out and describe the structure shift that occurs in Indonesian-English translation. This study also analized the accuracy of translations that contain structure shifts. The analysis was specifically directed to the thesis abstracts and their English translation version that taken from the library of Teacher Training and Education Faculty, Halu Oleo University. This study employed qualitative design. The total abstracts involved as source of data in this study were 2 abstracts that came from one study program, that is, Early-childhood Education. The analysis of the structure shift was based on the theory of Catford (1965). The result revealed that the structure shifts do exist in the translation of the thesis abstracts. Specifically, there are 10 structure shifts found in this study. Furthermore from these data, 4 of them are considered inaccurate translation; 5 are considered accurate translation; and only 1 is considered very accurate translation. This study concluded that the translator‟s comprehension about the target language system is highly required in order to produce an accurate translation. This study also suggests that the translation shifts shoud be included as one topic to be discussed in translation class. Keywords: Structure shift, Accuracy, Thesis Abstract